The meaningfulness of exploring one's own limits through interactions and enjoyment in outdoor high-intensity physiotherapy for people with multiple sclerosis: a qualitative study - Dahl, Stine Susanne Haakonsen; Arntzen, Ellen Christin; Normann, Britt (Frontiers in Rehabilitation Sciences, 2024)
Background and purpose Physical activity (PA) is often reduced in people with MS (pwMS), even when disability is low. Understanding the perspectives of pwMS on interventions aiming to improve PA is important to inform the development of such services. The aim of this study was to explore the experiences of pwMS participating in an outdoor, high-intensity and balance exercise group intervention. Methods This qualitative study was nested within an RCT exploring a novel intervention integrating sensorimotor exercises with high-intensity intervals of running/walking. Individual, in-depth interviews with the intervention group (n = 15; 12 women, 3 men; age 38–66; EDSS score 0–3.5) were conducted postintervention (mean days = 14), analyzed using a phenomenological-inspired approach with systematic text condensation, and interpreted based on enactive theory. Results Four categories were generated: (1) Exploration of one's own physical abilities: Challenging one's own limits was perceived by all participants to improve movement performance and/or intensity level. Such bodily changes engendered strong positive feelings. Some negative consequences of high-intensity training were described, increasing a feeling of loss. (2) New insights and beliefs: Participants experienced enhanced beliefs in their own capabilities, which they integrated in activities outside the intervention. (3) An engaging environment: The group setting was perceived as supportive, and the outdoor environment was perceived as stimulating activity. (4) Professional leadership, tailoring and co-creation of enjoyment: Physiotherapist-led, individualized interactions were regarded as necessary to safely revisit prior activities, such as running. Co-creating enjoyment facilitated high-intensity training and intervention adherence. Discussion High-intensity training combined with detailed exercises in a physiotherapy outdoor group was perceived to create meaningful bodily changes and enhance PA and prospects for both PA and life. Importantly, however, some negative experiences were also reported from the high-intensity training. Enactive theory allowed for the illumination of new perspectives: the importance of embodiment for self-efficacy and of tailored physiotherapy and an outdoor-group environment for exploring one's own limits to physical capabilities. These aspects should inform future exercise interventions in pwMS with low disability.